Occlusal Grinding Pattern during Sleep Bruxism and Temporomandibular Disorder - Yeni Wijaya; Laura S. Himawan; Roselani W. Odang (Faculty of Dentistry, Universitas Indonesia, 2013)
Sleep Bruxism is a significant etiology of temporomandibular disorder (TMD) and causes many dental or oral problems such as tooth wear or facet. There is no study analyzing the relationship between sleep bruxism and TMD. Objective: To investigate any relationship between occlusal grinding pattern during sleep bruxism and temporomandibular disorder. Methods: A cross-sectional study involving 30 sleep bruxism patients attended the Faculty Dentistry Universitas Indonesia Teaching Hospital (RSGMP FKG UI). Completion of 2 forms of ID-TMD index and questionnaire from American Academy of Sleep Medicine were done. BruxChecker was fabricated and used for two nights to record the occlusal grinding pattern. The occlusal grinding pattern was categorized into laterotrusive grinding (LG) and mediotrusive side. Further divisons of LG were: incisor-canine (IC), incisor-caninepremolar (ICP) and incisor-canine-premolar-molar (ICPM). Mediotrusive side was classified as mediotrusive contact (MC) and mediotrusive grinding (MG). Results: It was found that occlusal grinding pattern in non-TMD subjects were IC+MC, in subjects with mild TMD were ICP+MG and in subjects with moderate TMD were ICP+MG and ICPM+MG. TMJ was more significantly affected by ICP and ICPM grinding pattern than that of IC. Conclusion: There was a significant relationship between occlusal grinding pattern during sleep bruxism and TMD. DOI: 10.14693/jdi.v20i2.149